Uptake of HIV and AIDS services among lesbian, gay and bisexual identifying youths aged 18 to 35 years in Nairobi city county, Kenya - Lanyo, John; Orago, Alloys; Mugo, Judy (International Journal Of Community Medicine And Public Health, 2023)
Background: The study assessed the general uptake of HIV&AIDS care among the Lesbian, Gay, and Bisexual (LBG) identifying youths in Nairobi County. The focus was on sexual orientation and not gender identity. This research unpacked the depth in which socio-cultural, religious, systemic, personal attitudes and perceptions base contribute to the uptake of HIV&AIDS care and interventions to be scaled up. Methods: Descriptive cross-sectional design, involving qualitative and quantitative methods. The sample size was n=84 determined through the formula n=z2(1 –α/2)(1- P)/ɛ2P due to unknown nature and number of the target population in Nairobi. Used snowball sampling technique and a virtual snowball sampling to reach the population. Purposive sampling was applied to reach key informants. Descriptive statistical analysis was utilized reinforced by cross tabulation. Results: The uptake of HIV&AIDS services was 86% among the lesbian, gay and bisexual youths in Nairobi. The majority access HIV prevention and care services from government/public health facilities followed closely by NGO led facilities. Personal attitude and perception base play a significant role in utilization; 57% engaged in risky sexual activities. A majority (87%) of the respondents experienced injustices while accessing HIV&AIDS services attributed the experiences to their sexual orientation. Conclusions: The health care providers should be adequately trained to provide comprehensive, inclusive, non-judgmental services; policies evaluated to provide non-discriminatory services to eliminate stigmatization of the population. The findings intend to inform programming of HIV&AIDS for this subset of key population and bridge the knowledge gap.